2003
DOI: 10.1097/01.inf.0000095166.94823.11
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric gastrointestinal basidiobolomycosis

Abstract: Basidiobolomycosisis an unusual fungal infection that manifests in the skin and rarely involves other systems including the gastrointestinal tract. We retrospectively reviewed records of six pediatric patients (< or =14 years of age) diagnosed with gastrointestinal basidiobolomycosis from March 2000 to March 2002. Four patients came from the same region, suggesting environmental exposure. Basidiobolomycosis should be considered in the differential diagnosis in pediatric patients presenting with abdominal mass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 22 publications
3
43
0
Order By: Relevance
“…GI basidiobolomycosis is rare (Bittencourt et al, 1979;Khan et al, 1998), with only 14 cases in adults (Khan et al, 2001;Lyon et al, 2001) and 12 cases in children (Al Jarie et al, 2003;Wasim Yusuf et al, 2003) having been reported worldwide. The reported cases included eight cases from the United States; eight from the Kingdom of Saudi Arabia, four from Brazil, two each from Nigeria and Kuwait, one from Iran and one from the Netherlands (de Aguiar et al, 1980;Schmidt et al, 1986;Pasha et al, 1997;Khan et al, 1998;Smilack, 1998;Yousef et al, 1999;Zavasky et al, 1999;Al Jarie et al, 2003). No specific risk factors were identified for GI basidiobolomycosis, except that three patients had a history of diabetes mellitus (Khan et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GI basidiobolomycosis is rare (Bittencourt et al, 1979;Khan et al, 1998), with only 14 cases in adults (Khan et al, 2001;Lyon et al, 2001) and 12 cases in children (Al Jarie et al, 2003;Wasim Yusuf et al, 2003) having been reported worldwide. The reported cases included eight cases from the United States; eight from the Kingdom of Saudi Arabia, four from Brazil, two each from Nigeria and Kuwait, one from Iran and one from the Netherlands (de Aguiar et al, 1980;Schmidt et al, 1986;Pasha et al, 1997;Khan et al, 1998;Smilack, 1998;Yousef et al, 1999;Zavasky et al, 1999;Al Jarie et al, 2003). No specific risk factors were identified for GI basidiobolomycosis, except that three patients had a history of diabetes mellitus (Khan et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…It is a known cause of subcutaneous zygomycosis (Hocquet, 1979;Gugnani, 1999;Khan et al, 2001). Its aetiological role in GI infections is increasingly recognized (Al Jarie et al, 2003). The presenting symptoms of GI Basidiobolus infection include fever, vomiting, abdominal pain and weight loss.…”
Section: Introductionmentioning
confidence: 99%
“…Seven of them were from the KSA; six were reported by Al Jarie et al (2003) (Table 1). The seventh, reported by Hussein et al (2007), was a 13-year-old boy with GIB presenting with sudden-onset acute abdominal pain with diffuse abdominal rigidity and tenderness.…”
Section: Clinical Laboratory Imaging and Histopathological Findingsmentioning
confidence: 99%
“…Surgery and prolonged antifungal therapy are usually required for treatment (van den Berk et al, 2006). To the best of our knowledge, only 26 cases of GIB have been reported worldwide: 14 adult cases (eight from the USA, two from Brazil, two from Kuwait, one from Nigeria and one from the Netherlands; Kian Joe et al, 1956;Greer & Friedman, 1966;Dworzack et al, 1978;Zahari et al, 1990;Khan et al, 2001;Lyon et al, 2001) and 12 paediatric cases (eight from Saudi Arabia, two from Brazil, one from Iran and one from Nigeria; Zahari et al, 1990;Khan et al, 2001;Al Jarie et al, 2003;Wasim Yusuf et al, 2003). A report on the 12th paediatric case, which is the 8th paediatric case in the kingdom of Saudi Arabia (KSA), is in press (El-Shabrawi et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…GI basidiobolomycosis has been scarcely reported in the literatures and the total reported cases since 1964 till end 2012 were 44 cases worldwide. Recently, its etiologic role in gastrointestinal infections has been increasingly recognized in Saudi Arabia (Jarie et al, 2003;ElShabrawi et al, 2011;Hussein et al, 2007). To our knowledge 11 cases of GI basidiobolomycosis have been reported in Saudi Arabia: 10 cases in children and 1 case in young adult most of them came from southern region.…”
Section: Introductionmentioning
confidence: 99%